Estrutura populacional do caranguejo-uçá, Ucides cordatus, (Linnaeus, 1763) (Crustacea, Brachyura, Ocypodidae) e sustentabilidade do extrativismo na reserva extrativista do Mandira, Cananéia, São Paulo, Brasil - Pereira, Alineide Lucena Costa (Universidade Federal de São Carlos, 2010)
The exploitation of Ucides cordatus is an important economic activity for the artisanal fisherman along the Brazilian coast, despite of it the scientific knowledge about the population dynamic of this resource is yet insufficient for the management proposals in same regions. The artisanally harvest of the mangrove crab is the second more important economic activity in the Reserva Extrativista Mandira (25º 01 015 S; 48º 02 160 W). This paper aims to evaluate the extractivism of that resource, supplying subsidies to the implementation of management regulations. As a contribution for the management plan of the RESEX Mandira a study on Ucides cordatus population structure was carried out at four mangrove forests during 24 months. Crabs were monthly sampled from January of 2006 to December of 2007. The nature stock was estimated by monitoring the density of crabs burrow in the mangrove forests. The yield and commercial system was described through interviews with the fisherman and monitoring of the monthly yields. In the year of 2009, fifteen fishermen have the crab harvest as their mean economic resource, the RESEX yields an annual production of 6,7 ton. in the period of 1999 to 2008. CPUE increase in the analysis of the all study period. A total of 809 crabs was sexed, registered its width and length of carapace, and fresh weight. The overall sex ratio was skewed toward males (471 ind., 58,2 %), not different from the 1:1 expected proportion. The mean size (carapace width) for male was 61,7 mm (± 1,09) and for females 56,6 mm (± 0,85); the mean fresh weight was 112,61 g (± 51,34) for male and 79,13 g (± 24,65) for female. Males were major distributed in the size classes of 65 to 75 mm, and females occupied the smaller size classes (55 to 65 mm). Juveniles occurred along the year round, but were represented for few individuals. Males and females presented a large association between the carapace width and fresh weight, both sexes presented isometric relation between these variables. Mean crab density and biomass, in the years of 2006 and 2007, was 2,13 specimens/m2 and 229,7 ton/ km2 fresh mass or 1.731,5 ton. Only large males were commercially harvested, their biomass was 184,7 ton/ km2. The biomass could be different between the mangrove forest analyzed according to their environment characteristics, accessibility and fishing history. The mean crab abundance in the year of 2006 and 2007 was 16.054.404 specimens (1.337.867 dozens).
Keywords: Ecologia humana; Manejo participativo; Manguezais; Ecossistema de mangue; Reserva; Extrativista; Caranguejo-uçá; Ucides cordatus; Dinâmica populacional; Extractivist Reserve; Land crab; Ucides cordatus; Population dynamics; Mangrove; CIENCIAS BIOLOGICAS::ECOLOGIA